Treatment Technologies for Removal of Polyaromatic Hydrocarbon Compounds from Wastewater: A Review - Qasim M Jani; Hatem A Gzar; Mahdi Nuhair Rahi; Sadiq baqer (Wasit Journal of Engineering Sciences)
Industry discharges, home effluents, and/or urban runoff can all introduce polyaromatic hydrocarbon compounds (PAHs) into a treatment center. Regrettably, due to their chemical stability and resistance to biological degradation, PAHs are regarded as organic pollutants that persist. As a consequence, PAHs have indeed been identified as a possible source of skin, lung, and bladder cancer in humans. Due to PAHs' potential to cause cancer and/or mutation, their residues in treated wastewater are now subject to stricter legal regulation. adsorption ,membrane filtration, coagulation, electrocoagulation, flocculation, advanced oxidation reactions, phytoremediation and bioremediation process are some of the techniques used to remove PAHs from wastewater. In order to reduce environmental contamination, it is important to study different treatment technologies to treat wastewater. The aim of this paper is to highlighting and discussing some of treatment technologies for removing PAHs.